Penerapan dan Perluasan Co-Cultural Theory pada Pengalaman Komunikatif Pelaku Usaha Mikro - Indriastuti, Ana; Andika, Muhammad Fauzi Fitri (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
The market economy system, which is part of capitalism, involves power structures to maintain its dominance. Capitalism creates cultural groups based on socioeconomic class, including micro-entrepreneurs. This research focuses on micro-enterprises as a marginalized group in their efforts to improve their standard of living economically facing challenges in selling their products, especially in modern markets. Modern markets are controlled by dominant groups who practice capitalism by regulating the market economy to maintain their group dominance over other cultural groups. This research aims to explore the communicative practices of micro businesses using the Co-Cultural Theory framework in micro businesses located in Jakarta. The research was conducted using phenomenological methodology, interpretative paradigm, and qualitative approach. The results showed that Orbe's communicative practices were not fully fulfilled. Micro business actors have a tendency to communicate individually rather than in groups. Government support for Micro and Small Enterprises to create Substainable Debelopment Goals (SDGs) number 8 which aims to achieve decent work and economic growth has not been fully successful. The success of the communicative practices of shared cultural groups depends on the background, knowledge, culture, capital, and socio-economic conditions of micro-enterprises, there is a tendency for members of shared cultural groups to communicate independently rather than through groups, limited access or no access at all to communicate with dominant groups, and the importance of micro-enterprises having networking with dominant groups and other cultural groups to facilitate the marketing of their products.